INFLUENCE OF COVERT CARBOHYDRATE METABOLISM DISORDERS ON THE RISK OF KIDNEY FUNCTION DECLINE - N. T. Vatutin; M. I. Zinkovych; E. D. Yakubenko (Российский кардиологический журнал)
Aim. To assess the relation of covert carbohydrate metabolism disorders in patients with acute coronary syndrome (ACS) and declined kidney filtration after percutaneous coronary intervention (PCI).Material and methods. We compared the prominence of kidney filtration decline in patients after PCI with various grade of carbohydrate metabolism disorder.Results. Among 144 ACS patients, CIN was diagnosed significantly more frequently (44,8%) in the group with covert glucose intolerance. In the group with normal level of glycation of hemoglobin (<6,0%) CIN developed in 13,0% cases (p<0,001).Conclusion. The results point on that covert carbohydrate metabolism disorders play significant role in the development of kidney filtration decline.